A presentation of aids-related ophthalmic disease in a severely immunocompromised patient - Chetrit, Sally (Canadian Journal of Optometry, 2010)
Background: Human immunodeficiency virus (HIV) retinopathy is the most common ocular manifestation of the acquired immunodeficiency syndrome (AIDS), serving as an important marker for patients with significantly compromised immune status who are at risk for developing severe and visionthreatening ocular opportunistic infections. This case report describes a presentation of HIV retinopathy and cytomegalovirus (CMV) retinitis, and reviews the current management options. Case Report: A 40-year-old black male presented for a comprehensive eye exam to rule out HIV-related ophthalmic disease. At his initial visit, a dilated fundus examination revealed HIV retinopathy of the left eye. Upon subsequent examinations and as his immune status diminished, the patient developed CMV retinitis of the right eye. The patient was treated successfully with a course of highly active antiretroviral therapy (HAART) and oral valgancyclovir. Conclusion: CMV retinitis is the most common ocular opportunistic infection associated with AIDS. Treatment with systemic HAART and concomitant anti-CMV therapy leads to reconstitution of the immune system and regression of the retinitis.